Targeting CD73 and correcting adenosinergic signaling in critically ill patients - Lunderberg, Justin Mark; Spicer, Alexander James; Cassavaugh, Jessica; Jalkanen, Juho; Haskó, György; Robson, Simon C. (Frontiers in Pharmacology, 2026)
The concept of the intensive care unit (ICU) was developed around 70 years ago, and this has become essential for caring for a hospital’s sickest patients. A commonality for many patients’ critical illness is the systemic inflammatory state with multiple-organ injury precipitated by infectious causes and/or other pathophysiologic insults. Therapeutic modalities to address these complications remain unclear, and there are no FDA-approved drugs to treat these often-devastating clinical situations. Clinical deterioration may be associated with the release of “damage-associated molecular patterns” (DAMPs), such as extracellular adenosine triphosphate (eATP), from stressed and dying cells. Pharmacological dosing or boosting of CD73, an ectoenzyme that can convert pro-inflammatory adenosine monophosphate (AMP) to anti-inflammatory adenosine, in this setting of critical illness has been shown to have a survival benefit with decreased time in the hospital and ICU. Whether there are clinical benefits of extracellular nucleotide (eATP) scavenging over adenosine generation within the setting of inflammatory diseases remains unclear. Upcoming pre-clinical developments testing soluble forms of CD39 to hydrolyze eATP to AMP in sepsis and following cardiac surgery should clarify this question. We conclude by suggesting that exogenous CD39, CD73, and/or other ectonucleotidases may provide therapeutic benefits in critically ill patients.